Development of test equipment to study life, friction and wear performance for polymer gears in automotive applications - Sofian, Azizul Helmi (2017)
Polymer materials are widely employed in drives of machines and mechanisms owing to their advantages over metals: high specific mechanical properties and tribological performance, self-lubrication, high resistance to impact loading and its damping, resistance to oils and chemicals, high size-weight ratio, high production rates in case of mass production and high safety. This study is aim to fabricate biopolymer gear and polymer gear by study the wear behavior of biopolymer gear and polymer gear. These gear are produced from Polylactic acid (PLA) and Acrylonitrile Butadiene Styrene (ABS) which undergo fabrication process by injection molding process. After fabrication process, the gears are tested by using gear test rig with different RPM for 4 hours. Parameters that are varied for this experiment is RPM and load. First experiment is testing the gear with different material and different RPM. Three different RPM are been used for this experiment which are 500 RPM, 1000 RPM, and 1500 RPM. Second experiment is using the different gear material and different RPM but with added 10N load. Third experiment is to know gear durability and to compare biopolymer gear and polymer gear. There are four type of failure characteristics to study in this experiment which are gear wear debris formation, microstructure surface condition monitoring, weight loss and thermal damage.